N-type pyrazine and triazole-based luminogens with aggregation-enhanced emission characteristics1. Issue 53 (7th July 2015) - Chen, Ming; Li, Lingzhi; Nie, Han; Shi, Yang; Mei, Ju; Wang, Jian; Sun, Jing Zhi; Qin, Anjun; Tang, Ben Zhong
<x xml:space="preserve">Abstract</x> N-type pyrazine and triazole-based AIEgens that could readily form red-emissive complexes with triphenylamine in the aggregate state were facilely prepared by click reactions.